2009
DOI: 10.2174/1874306400903010100
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Daily Albuterol in Infants with a History of Bronchospasm: A Multi-Center Placebo Controlled Trial

Abstract: Introduction:Inhaled short-acting bronchodilators are recommended for the quick relief of bronchospasm symptoms in children including those less than five years of age. However, limited safety data is available in this young population.Methods:Safety data were analyzed from a randomized, double-blind, parallel group, placebo-controlled multicenter, study evaluating albuterol HFA 90µg or 180µg versus placebo three times a day for 4 weeks using a valved holding chamber, Aerochamber Plus and facemask in children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
1
0
3
Order By: Relevance
“…Literatürde salbutamol sonrası PR intervalinde anlamlı değişiklik tespit edilen çalışma yoktur. Hedrick ve ark (19). tarafından yapılan çok merkezli randomize kontrollü bir çalışmada 24 ay altı bronkospazm kliniği ile gelen hastalarda salbutamol 90 mcg, 180 mcg ve plasebo grupları 4 hafta boyunca günde 3 tedavi dozu verilerek izlenmiş, başlangıçta ve 4. hafta sonunda salbutamol öncesi ve sonrası EKG değerlendirmelerinde PR intervallerinde 4. hafta sonunda başlangıca göre ve tek doz salbutamol sonrasında öncesine göre anlamlı farklılık bulunamamıştır.…”
Section: Tablo II Grupların Elektrokardiografik Bulgularının Karşılaunclassified
See 1 more Smart Citation
“…Literatürde salbutamol sonrası PR intervalinde anlamlı değişiklik tespit edilen çalışma yoktur. Hedrick ve ark (19). tarafından yapılan çok merkezli randomize kontrollü bir çalışmada 24 ay altı bronkospazm kliniği ile gelen hastalarda salbutamol 90 mcg, 180 mcg ve plasebo grupları 4 hafta boyunca günde 3 tedavi dozu verilerek izlenmiş, başlangıçta ve 4. hafta sonunda salbutamol öncesi ve sonrası EKG değerlendirmelerinde PR intervallerinde 4. hafta sonunda başlangıca göre ve tek doz salbutamol sonrasında öncesine göre anlamlı farklılık bulunamamıştır.…”
Section: Tablo II Grupların Elektrokardiografik Bulgularının Karşılaunclassified
“…Del Rio Navarro ve ark (22)'nın yaptığı çalışmada astım tanısı ile izlenmekte olan, ortalama yaşı 7.4 olan 30 çocuğa 0.15 mg/kg dozunda 10 dakika ara ile iki kez salbutamol nebulize verilmiş ve EKG değerlendirmesinde QTc mesafesinin 397 msn'den 418 msn'ye yükseldiği belirtilmiştir. Bir başka çalışmada ise 24 ay altı bronkospazm kliniği ile acile getirilen hastalarda salbutamol 90 mcg ve 180 mcg gruplarında tek doz ilaç sonrasında öncesine göre ve 4 haftalık tedavi sonrasında başlangıca göre QTc mesafesinde anlamlı farklılık saptanmadığı belirtilmiştir (19). Bizim çalışmamızdaki QTc uzamasının tek doz grubunda değil, üç doz grubunda olmasının β2 reseptör doygunluğunun üç doz salbutamol ile artmasına bağlı olabileceğini düşünmekteyiz.…”
Section: Tablo II Grupların Elektrokardiografik Bulgularının Karşılaunclassified
“…En algunos estudios se ha descrito que los β2 agonistas pueden tener como efectos secundarios la agitación y la intranquilidad (63). Esta situación, en teoría, podría aprovecharse en algunos deportes de contacto y de combate, con lo cual se tendría cierta ventaja sobre los contrincantes.…”
Section: Efectos De Los β2 Agonistas En El Rendimiento De Los Deporti...unclassified
“…The incidence and risk factors of developing SVT after treatment with SABA are currently unknown. Although SABA is a selective β-2 agonist, significant cardiac arrhythmias may result from their use; in a study with salbutamol in 83 children, no significant arrhythmias were triggered [ 11 ], while other studies showed that fenoterol increased the heart rate more than salbutamol and terbutaline [ 12 , 13 ]. β-2 agonists increase the rate of conduction across the AV node [ 14 ], and their use may lower the threshold for reentry and trigger episodes of SVT.…”
Section: Introductionmentioning
confidence: 99%